Sjögren Syndrome Complicated by Mucosa-Associated Lymphoid Tissue Lymphoma and Lymphocytic Interstitial Pneumonia - Ahmed, Fatma; Raslan, Osama; Muzaffar, Razi; Parkar, Nadeem; Marwaha, Nitin; Osman, Medhat M. (Frontiers in Oncology, 2015)
Sjögren syndrome (SS) is an autoimmune disease with exocrine glands dysfunction and multiorgan involvement. It is associated with increased risk of lymphoproliferative disorders, especially B-cell marginal zone lymphoma. While the role of F-18 Fluorodeoxyglucose position emission tomography/computed tomography (F-18 FDG PET/CT) for evaluation of lymphoma has been established, its use in patients with a chronic history of SS to evaluate for possible lymphoproliferative disorders or multiorgan involvement is limited. We present a case of chronic SS in which F-18 FDG PET/CT demonstrated FDG avid intraparotid and cervical lymph nodes pathologically proven to be mucosa-associated lymphoid tissue lymphoma. In addition, the patient had bibasilar cystic changes consistent with lymphocytic interstitial pneumonia.